Development and evaluation of a 3d printed training model for endoscopic third ventriculostomy in low-income countries - Pablo González-López; Cristina Gómez-Revuelta; Martin Puchol Rizo; Iván Verdú Martínez; Jaime Fernández Villa de Rey Salgado; Jesús Lafuente; Eduardo Fernández-Jover; Víctor Fernández-Cornejo; Juan Nieto-Navarro (Brain and Spine, 2023)
Introduction: Pediatric hydrocephalus is highly prevalent and therefore a major neurosurgical problem in Africa. In addition to ventriculoperitoneal shunts, which have high cost and potential complications, endoscopic third ventriculostomy is becoming an increasingly popular technique especially in this part of the world. However, performing this procedure requires trained neurosurgeons with an optimal learning curve. For this reason, we have developed a 3D printed training model of hydrocephalus so that neurosurgeons without previous experience with endoscopic techniques can acquire these skills, especially in low-income countries, where specific techniques training as this, are relatively absent. Research Question: Our research question was about the possibility to develop and produce a low-cost endoscopic training model and to evaluate the usefulness and the skills acquired after training with it. Material and Methods: A neuroendoscopy simulation model was developed. A sample of last year medical students and junior neurosurgery residents without prior experience in neuroendoscopy were involved in the study. The model was evaluated by measuring several parameters, as procedure time, number of fenestration attempts, diameter of the fenestration, and number of contacts with critical structures. Results: An improvement of the average score on the ETV-Training-Scale was noticed between the first and last attempt (11.6, compared to 27.5 points; p<0.0001). A statistically significant improvement in all parameters, was observed. Discussion and Conclusion: This 3D printed simulator facilitates acquiring surgical skills with the neuroendoscope to treat hydrocephalus by performing an endoscopic third ventriculostomy. Furthermore, it has been shown to be useful to understand the intraventricular anatomical relationships.